Novel Design of Power Generation with Windmill Using National Grid (International Journal of Innovative Research in Engineering & Management, 2021)
When it comes to expanding its national grid and electrifying  every corner of its land, India, a rapidly growing country, is  always trying to do so. Most of India's energy is produced by  large power plants, which are subsequently distributed through  a number of grids and networks. India's energy infrastructure is  the best in the world. Electricity dependability is a challenge in  some of the most distant or hard-to-reach locations. It is  common for power outages to occur in these areas, as well as  low supply voltages. It is possible to create clean energy using  windmills when the wind blows constantly at an extremely low  cut-in speed. Turbines and generators convert the stored wind kinetic energy  into electricity in wind farms These facilities create electricity  dependent on how fast the winds are blowing at them. As part  of the investigation, a windmill was connected to the existing  system to generate electricity. There is no need for external  battery banks in order for the system to function properly. Once  a specific threshold is reached, the windmill will take care of  its load, and the extra energy will be sent back into the power  grid. Every time the windmill can't keep up, we'll have to turn to the  grid. Net metering is used for electricity exchange. The model  is used to analyze the study's validity and other technical  features. To increase supply dependability, the size of  windmills and other grid balancing elements will be adjusted as  part of the initiative.
Keywords: Electrical energy; Grid; Threshold; Shortfall; Windmill; Balance of systems